Euglenophyta from a stream of Pampean plain subjected to anthropic effects: Aº Rodriguez, Buenos Aires, Argentina - Conforti, Visitacion Teresa D. (2009)
Eighty nine taxa of Euglenophyta, sampled in Rodríguez Stream, Buenos Aires, Argentina, 2 belonging to the genus Euglena Ehr., 7 to Lepocinclis Perty, 14 to Phacus Duj., 40 to Strombomonas Defl. and 26 to Trachelomonas Ehr. have been identified. Besides 12 loricate taxa were examined by scanning electron microscopy (SEM). Details of their envelope ultrastructure are illustrated.